Molecular characterization of two novel mutations causing factor XI deficiency: A splicing defect and a missense mutation responsible for a CRM+ defect - Guella, Ilaria; Soldà, Giulia; Spena, Silvia; Asselta, Rosanna; Ghiotto, Rossella; Tenchini, Maria Luisa; Castaman, Giancarlo; Duga, Stefano (Thrombosis and Haemostasis, 2008)
Severe factor XI (FXI) deficiency is a bleeding disorder generally inherited as an autosomal recessive trait and characterized by haemorrhagic symptoms mainly associated with injury or surgery. So far, more than 150 causative molecular defects have been identified throughout the F11 gene. In the present study, we investigated the molecular basis of FXI deficiency in two Italian patients. Mutational screening of the F|| gene disclosed a novel missense substitution (Arg184Gly) in exon 7 and two splicing mutations: a novel G>A transition affecting the last nucleotide of exon 4 (325G>A), and the already known IVS6+3A>G. RT-PCR assays were performed on total RNA extracted from platelets and lymphocytes of each patient. Se- quencing of RT-PCR products demonstrated that both 325G>A and IVS6+3A>G mutations abolish the corresponding donor splice site, causing the skipping of the affected exon; this in turn results in a frameshift introducing a premature termination codon. Expression of recombinant FXI-Arg184Gly revealed a 70% reduction in FXI activity, suggesting that the Arg184Gly mutation might cause a cross-reactive material positive (CRM+) deficiency. In conclusion, the functional consequences of two splicing mutations leading to FXI deficiency have been elucidated. Moreover, we report a novel missense mutation in the FIX-binding region of the FXI A3 domain leading to a CRM+ deficiency.
Keywords: FXI deficiency; mutational screening; expression experiments; splicing mutations; CRM+ defects